2018
DOI: 10.1111/jerd.12439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and storage time on dental bleaching effectiveness

Abstract: Objective To evaluate the effect of storage time and temperature on the effectiveness of bleaching agents. Methods Enamel slabs were randomly allocated according to the concentration of carbamide peroxide (CP): 10% (CP10) and 16% (CP16). Shade evaluations were conducted at baseline and then after 3 and 12 months of storage at 3 different temperatures: 10°C (±2°C), 25°C (±2°C), and 35°C (±2°C). Objective color evaluation was performed (spectrophotometer CIEL*a*b* system and CIEDE2000) to calculate the color cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…Thus, VL was more effective for removing red and yellow polyphenolic chromophores present in tea, reinforcing the theory that violet wavelength would interact with external discoloration . In addition, staining methods have been extensively used in several bleaching studies in order to standardize color parameters . In this sense, a * and b * variations indicated that changes promoted in the control could have been caused by the detachment of staining molecules during artificial saliva storage, but this group presented statistically lower color change in comparison with the others.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, VL was more effective for removing red and yellow polyphenolic chromophores present in tea, reinforcing the theory that violet wavelength would interact with external discoloration . In addition, staining methods have been extensively used in several bleaching studies in order to standardize color parameters . In this sense, a * and b * variations indicated that changes promoted in the control could have been caused by the detachment of staining molecules during artificial saliva storage, but this group presented statistically lower color change in comparison with the others.…”
Section: Discussionsupporting
confidence: 54%
“…Change in tooth color may occur due to a natural process of dental aging or may be caused by oral diseases, dental trauma or by the use of dental material such as mineral trioxide aggregate [7][8][9][10] . Moreover, tooth discoloration may also be due to extrinsic pigmentation, which occurs with the consumption of highly pigmented foods and also tobacco use 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature showed that while different concentration agents exhibit similar efficacy 12 , the use of therapies with lower peroxide concentration has been recommended as the first choice because they usually are associated with less sensitivity during treatment 19 . Moreover, an in vitro study showed that higher concentrations of peroxide in bleaching materials can degrade more easily than peroxides with lower concentrations and thus affect its effectiveness 8 . In fact, 60.5% of dentists choose the in-office protocol, of which 50% indicated CP 37% or HP 37% and 10.5% indicated the CP 10-22%, concentrations used to at-home.…”
Section: Discussionmentioning
confidence: 99%
“…These products are mainly based on hydrogen peroxide (HP) or carbamide peroxide (CP), which breaks down into HP and urea. These oxidizing chemical agents can be used for vital or nonvital tooth bleaching; while sodium perborate (SP) is used exclusively for nonvital tooth bleaching [8][9][10] . Moreover, low concentration agents [10-22% CP and 6% HP] are used at home by the patients under professional supervision, which is defined as an at-home technique; and high concentrations [>30% CP or HP] are applied only in the dental office by the dentist in the so-called in-office technique 11 .…”
Section: Introductionmentioning
confidence: 99%